Relative heritage language and majority language use before school start explains variance in 2nd grade majority language but not reading skills - Højen, Anders; Bleses, Dorthe (Frontiers in Psychology, 2023)
The present study examined whether parents’ and bilingual children’s own relative use of the heritage language vs. the majority language in the homes of bilingual children in Denmark before school start explains variance in 2nd grade majority language skills and reading skills. The study included two groups of children: the Mixed bilinguals group (defined by having a native Danish and a nonnative parent, N = 376) and the Heritage bilinguals group (defined by having parents who were both speakers of a Heritage language, N = 276). Four-stage hierarchical regression analyses showed that, after accounting for type of bilingualism, socioeconomic status (SES) and home literacy environment quality, relative use of the heritage vs. the majority language explained variance in 2nd grade Danish language comprehension scores, but did not explain variance in two reading scores, namely decoding and reading comprehension. In addition, a home literacy factor denoting book exposure (number of books, frequency of reading, library visits, and age of beginning shared book reading) was a significant predictor of both 2nd grade language and reading outcomes, whereas SES became a nonsignificant predictor when adding home literacy and language use predictors. We interpret the results to mean that parents’ and the child’s own relative use of the heritage language vs. the majority language before school start does not influence bilingual children’s early reading skills, whereas supportive early home literacy environment is a positive predictor of reading skills independently of SES and parental majority language use and skill.